Influence of molarity and chemical composition on the development of compressive strength in POFA based geopolymer mortar - Kabir, S.M.A.; Alengaram, Ubagaram Johnson; Jumaat, Mohd Zamin; Sharmin, A.; Islam, A. (Hindawi, 2015)
The investigation concerns the use of the optimum mix proportion of two locally available pozzolanic waste materials, namely, ground granulated blast furnace slag (GGBS) and palm oil fuel ash (POFA), together with metakaolin (MK) as binders. In addition, another local waste material, manufactured sand (M-sand), was used as a replacement for conventional sand in the development of green geopolymer mortar. Twenty-four mortar mixtures were designed with varying binder contents and alkaline activators. The oven dry curing was also kept consistent for all the mix proportions at a temperature of 65 degrees C for 24 hours. The highest 28-day compressive strength of about 48 MPa was obtained for the mortar containing 20 of MK, 35 of GGBS, and 45 of POFA. The increment of MK beyond 20 leads to reduction of the compressive strength. The GGBS replacement beyond 35 also reduced the compressive strength. The entire specimen achieved average 80 of the 28-day strength at the age of 3 days. The density decreased with the increase of POFA percentage. The finding of this research by using the combination of MK, GGBS, and POFA as binders to wholly replace conventional ordinary Portland cement would lead to alternate eco-friendly geopolymer matrix.